The model of participation knowledge management for pomelo in Nakhon Pathom province. - Rittiboonchai et al., Wisit (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The research has two main objectives: 1) to study the problems in participate knowledge management model for pomelo in Nakhon Pathom Province 2) to create model of participation knowledge management model for pomelo in Nakhon Pathom province. This research all qualitative research approach. The subjects of this study were classified into two groups: 1) the pomelo growers in Nakhon pathom province 20 persons 2) those involved with pomelo Pathom province 10 persons with a purposive sampling. The study found that. The issue of the problems in participate knowledge management model for pomelo in Nakhon Pathom Province. (1) How to grow pomelo has inherited from his ancestors from generation to generation. Without improved. (2) development and learning ways was trial and error. (3) exchanging knowledge in a narrow and among relatives only The building model was as follows. (1) To spread Knowledge Experience and availability to the farmers. And those who have a vested interest Sustainable benefits to the grapefruit crop circles in Nakhon Pathom next. (2) To Distribution pattern knowledge required to make a written record to modify into explicit knowledge back to those who are interested to know the future remain. Article history : Accepted 17 September 2016 SIMILARITY INDEX = 2.41